2018
DOI: 10.4149/bll_2018_026
|View full text |Cite
|
Sign up to set email alerts
|

Tumour metabolic activity measured by fluorodeoxyglucose positron emission tomography for radiotherapy planning as a prognostic factor for locally advanced non-small cell lung cancer

Abstract: OBJECTIVES: To analyse whether the maximum standardized uptake value of the positron emission tomography/computed tomography for radiotherapy planning was useful as a prognostic factor for tumour response and survival of patients with locally advanced non-small cell lung cancer. BACKGROUND: Increased 18F-fl uoro-2-deoxyglucose uptake by lung cancer cells, measured as the maximum standardized uptake value, has been reported to predict the biologic aggressiveness of both early and advanced non-small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…27 Masarykova et al found a correlation between the maximum standardized uptake value and the patient prognosis and lung cancer aggressiveness. 28 Our previous study found the standard uptake value of primary tumor was associated with LN size, which may explain why the patients with LN enlargement in N0 staging had a worse CSS. We speculated the SUVmax value and LN size could synergistically predict the prognosis of NSCLC patients with negative LN, which need more PET/CT information to analyze.…”
Section: Discussionmentioning
confidence: 90%
“…27 Masarykova et al found a correlation between the maximum standardized uptake value and the patient prognosis and lung cancer aggressiveness. 28 Our previous study found the standard uptake value of primary tumor was associated with LN size, which may explain why the patients with LN enlargement in N0 staging had a worse CSS. We speculated the SUVmax value and LN size could synergistically predict the prognosis of NSCLC patients with negative LN, which need more PET/CT information to analyze.…”
Section: Discussionmentioning
confidence: 90%